Specifics of the employment of higher education teachers - Tancer Verboten, Mojca (Studia Historica Slovenica, 2022)
Based on the selected materials addressing the procedure and requirements for the employment of higher education teachers in the context of different higher education systems, the paper presents specifics related to the post of a higher education teacher that are absent in the cases of employment of workers in other industries. Three aspects will be examined: the concept and status of higher education teachers, the conditions for filling the post of a higher education teacher, and the procedure for the employment of higher education teachers. The primary hypothesis of the paper is that requirements and procedure for the employment of higher education teachers should necessarily be regarded, interpreted, and legally regulated by taking into consideration specific characteristics of the status of higher education teachers employed at a university, the latter being an institution with a special status derived from the institutional autonomy
Keywords: conditions of employment; delovno pravo; employment of higher education teachers; habilitation; izvolitev v naziv; odprti karierni model; open vacancy model; pogoji za zaposlitev; Slovenija; tenure track model; visokošolski učitelji; zaposlovanje; zaprti karierni model